Platelet rich fibrin: A novel treatment for trophic ulcer in Hansen's disease. (April 2022) - Dorjay, Konchok; Tandon, Sidharth; Singh, Ajeet; Sharma, Satish; Sardana, Kabir
Patients with Hansen's disease are liable to develop non-healing trophic ulcers. The aim of this study was to determine the efficacy of autologous platelet rich fibrin (PRF) applied at weekly intervals in the management of trophic ulcers. The mean age of the patients, duration and size of ulcer were 44.3 years, 7.4 months and 6.25cm 2 respectively. After the third sessions of weekly dressing, there was a significant reduction in the ulcer area (p value = 0.015). All ulcers healed by a maximum of six weeks. No adverse events were noted. PRF thus seems a feasible, safe, simple and cost-effective treatment method.